Peningkatan pemahaman konsep perjuangan mempertahankan kemerdekaan Indonesia melalui model pembelajaran kooperatif tipe group investigation kelas V sekolah dasar - Tri Yuda Bekti Pamungkas; Karsono Karsono; Fadhil Purnama Adi (Didaktika Dwija Indria, 2019)
Abstract. The purpose of research design was to improve the understanding about concepts the struggle to defend Indonesia's independence by applying Group Invetigation models. Two cycles was used in this research design amount teacher and 5th grade of primary school of SD N Pulisen Boyolali conduct of 35 students as the subject research. The data collecting techniques were test, observation, interview, and documentation. And the analyze data used interactive technique. The average score of class before action (pre-cycle) is 31, in cycle 1 the average score increase become improves 64,8, and in cycle 2 increase 75,1. The conclusion was drawn that applying GI model can work up the understanding about concepts the struggle to defend Indonesia's independence in 5th grade of primary school of SD N Pulisen Boyolali 2018/2019.Keywords: Group Investigation, understanding about concepts, the struggle to defend Indonesia's independence, Elementary School.